(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Jump formwork is the latest technology used for construction of high rise building. This paper analysis the comparison of conventional and jump formwork with a live project to compare the various parameters. This paper studies the role of advanced formwork systems in high-rise construction and analyzes this role in shaping not only the progress of concrete activities, but the entire construction sequence.